2019
DOI: 10.26822/iejee.2019349249
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Whatsapp Usage on the Attitudes of Students Toward English Self-Efficacy and English Courses in Foreign Language Education Outside the School

Abstract: The aim of this study is to examine if using WhatsApp actively in English outside the school has any effect on the students' attitudes and self-efficacy belief on English course. In this study, a sequential explanatory pattern was used. In order to obtain quantitative data, one group pretest-posttest design was used. The participants consist of 11th grade students studying in an Anatolian High School in the center of Sivas. The implementation of the study lasted eight weeks. In terms of the experiment, WhatsAp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…The study found that using WhatsApp outside the English course had a significant effect on students' self-efficacy beliefs in reading and listening. Moreover, the interview revealed that students experienced emotions of happiness, pride, and joy from using the WhatsApp application in the experiment (Çam & Can, 2019). The correlation between WhatsApp and students' motivation in language learning/teaching has also been reviewed in many studies (Alamer, 2016;Bensalem, 2018;Han & Keskin, 2016;Khan, 2016).…”
Section: Whatsapp's Effect On Students' Attitudes Motivation and Anxmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that using WhatsApp outside the English course had a significant effect on students' self-efficacy beliefs in reading and listening. Moreover, the interview revealed that students experienced emotions of happiness, pride, and joy from using the WhatsApp application in the experiment (Çam & Can, 2019). The correlation between WhatsApp and students' motivation in language learning/teaching has also been reviewed in many studies (Alamer, 2016;Bensalem, 2018;Han & Keskin, 2016;Khan, 2016).…”
Section: Whatsapp's Effect On Students' Attitudes Motivation and Anxmentioning
confidence: 99%
“…Some studies conducted in Saudi context have focused either on the efficacy of WhatsApp on English language learning/teaching or the effect of WhatsApp on students' motivation (Ahmed & Hassan, 2019;Çam & Can, 2019;Hamad, 2017;Nasr & Mustafa, 2018). A study examined the effects of Skype, YouTube, and WhatsApp on developing the speaking skills of Saudi EFL students.…”
Section: Whatsapp In the Saudi Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that using WhatsApp outside the English course had a significant effect on students' self-efficacy beliefs in reading and listening. Moreover, the interview revealed that students experienced emotions of happiness, pride, and joy from using the WhatsApp application in the experiment (Çam & Can, 2019). The correlation between WhatsApp and students' motivation in language learning/teaching has also been reviewed in many studies (Alamer, 2016;Bensalem, 2018;Han & Keskin, 2016;Khan, 2016).…”
Section: Whatsapp's Effect On Students' Attitudes Motivation and Anxmentioning
confidence: 99%
“…We have a lot of social media application such as Whatsapp, Instagram, Wechat and a lot more, we can connect with each other among our friends [1][2][3][4]. The rise of specific apps for social media engagement also quite large such as LinKedIn and few others have motivated others to develop very specific social media platform [5][6][7][8][9][10][11][12]. Thus, in this project we have developed a portal for student to engage in active or passive discussion among them that act just like other social media with multiple functions.…”
Section: Introductionmentioning
confidence: 99%